Analysis of dentin wear and biological properties promoted by experimental inoffice desensitizing materials - Fernanda de Souza Silva Ramos; Laryssa de Castro Oliveira; Larissa Albertinazzi; Sávio José Cardoso Bezerra; Vanessa Rodrigues dos Santos; Tais Scaramucci; Cristiane Duque; Bernhard Ganss; Marina Trevelin Souza; Juliano Pelim Pessan; Ticiane Cestari Fagundes (BMC, 2024)
Abstract Background This study aimed to evaluate dentin wear and biological performance of desensitizing materials. Methods Seventy bovine root dentin blocks were sectioned. Half of the surface of each specimen was untreated (control) and the other half was immersed in EDTA and treated with the following desensitizing materials: placebo varnish (PLA), fluoride varnish (FLU), sodium fluoride (NaF) varnish + sodium trimetaphosphate (TMP), universal adhesive (SBU), S-PRG varnish (SPRG), biosilicate (BIOS), and amelotin solution (AMTN). After application, the specimens were submitted to an erosive-abrasive challenge and the wear analyzed by optical profilometer. Serial dilutions of extracts obtained from the culture medium containing discs impregnated with those desensitizers were applied on fibroblasts and odontoblasts-like cells cultures. Cytotoxicity and production of total protein (TP) by colorimetric assays were determined after 24 h. Data were statistically analyzed using Kruskal-Wallis, Dunn's, One-way ANOVA and Tukey tests (p ≤ 0.05). Results No dentin wear was observed only for SBU. The lowest dentin wear was observed for AMTN and TMP. Cell viability was significantly reduced after treatment with undiluted extracts of PLA, FLU, TMP and SBU in fibroblasts and TMP and SBU in odontoblast-like cells. SPRG, BIOS and AMTN were cytocompatible at all dilutions tested. Considering TP results, no statistical difference was observed among the groups and high levels for TP were observed after TMP and FLU treatments. Conclusions Universal adhesive system may protect dentin with opened tubules from wear after challenge. Extracts of adhesive and fluoride varnishes presented cytotoxic mainly on fibroblasts. The enamel protein may be a future alternative to treat dentin with opened tubules because it may cause low wear under erosive-abrasive challenge with low cytotoxic effects.